Two adjacent individual fibroepithelioma of Pinkus of the umbilicus-one pink, one pigmented-a case report and review of the literature - Mike Inskip; Caterina Longo; Afaf Haddad (Mattioli1885, 2016)
We present a unique case of separate and independent adjacent fibroepitheliomas of Pinkus (FeP) arising from the umbilicus in an 83-year-old man. Of further interest, one is pigmented and the other nonpigmented. Clinical, dermatoscopic and histopathological images are provided. A review of the published literature is undertaken to attempt to assess the incidence of pigmented versus nonpigmented FeP. Of 24 published FeP cases, 10 (41.7%) have been pigmented. Thus to date pigmented FeP comprise approaching one-half of all reported cases.